2020
DOI: 10.1021/acs.jafc.0c00242
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidins-Loaded Complex Coacervates for Improved Stability by Self-Crosslinking and Calcium Ions Chelation

Abstract: The purpose of this work was to develop a facile strategy based on self-crosslinking between the core and wall materials in the coacervation system for effective procyanidins (PCs) encapsulation. The coacervates were constructed through the interaction of bioactive PCs, gelatin, and sodium alginate, followed by forming cationic bridge of sodium alginate-calcium ions to improve the stability of PCs. When the concentration of PCs and calcium ions were 6.25 and 0.24 mg/mL, respectively, the PCloaded coacervates s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…Moreover, the fluorescence intensity ratio between JC-1 aggregates and JC-1 monomers showed that CE-TPP 12.5:1 -AST could significantly protect the mitochondrial membrane potential in NRK cells, compared with CE-AST (Figure D). We recently reported that the mitochondrial membrane potential fluorescence imaging could also be used to monitor the protective effect of encapsulated procyanidin for PC-12 cells against H 2 O 2 . The results of fluorescence imaging for mitochondrial membrane potential herein further suggested that CE-TPP 12.5:1 -AST exhibited an enhancement in protecting live cells against oxidation.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Moreover, the fluorescence intensity ratio between JC-1 aggregates and JC-1 monomers showed that CE-TPP 12.5:1 -AST could significantly protect the mitochondrial membrane potential in NRK cells, compared with CE-AST (Figure D). We recently reported that the mitochondrial membrane potential fluorescence imaging could also be used to monitor the protective effect of encapsulated procyanidin for PC-12 cells against H 2 O 2 . The results of fluorescence imaging for mitochondrial membrane potential herein further suggested that CE-TPP 12.5:1 -AST exhibited an enhancement in protecting live cells against oxidation.…”
Section: Resultsmentioning
confidence: 73%
“…The C–H and CO stretching vibration peaks of MCT appeared at 2933.4 and 1746.8 cm –1 , respectively. The peaks at 1659.5 and 1536.2 cm –1 represented the amide I band (CO and N–H stretching vibration peaks) and amide II band (N–H and C–H stretching vibration peak), respectively. , Compared with that of CE, the absorption peaks of the amide I and amide II bands of CE-TPP 12.5:1 were significantly enhanced, indicating the formation of amide bonds between TPP and CE. The conformational change in TPP-modified CE was further confirmed by circular dichroism (CD) spectroscopy.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The method for evaluating the stability of FX and FX@PVP NPs was slightly modified according to Tie et al [38] and Liu et al [39]. The thermal stability was assessed by placing equal volumes (1 mL) of samples in a water bath at different temperatures (40, 50, 60 • C) for 24 h, then the contents of FX in freeze-dried samples were determined by HPLC.…”
Section: Stability Of Fx@pvp Npsmentioning
confidence: 99%
“…In order to prepare hydrogels into implantable scaffold with different mechanical, degradation, and slow-release properties, the cross-linking process needs to be adjusted. Because of the covalent bonds presented between the polymer chains, chemical cross-linking is one of the highly resourceful methods for the formation of hydrogels with excellent mechanical strength ( Tie et al, 2020 ). The hydrogel formed in this method usually degrades slower, so that the release rate of the carried immune drug is relatively slow.…”
Section: Characteristics Of Hydrogels As Delivery Systems For Cancer Immunotherapymentioning
confidence: 99%